Media Discourse and the Framing of Gulf Elite Connections in the Epstein Case: A Comparative Study of France24 Arabic and WatanOnline - Ammar, Zaqhlul; Ula, Aristya Luna Rahmatul; Jannah, Miftachul; Al Anshory, Abdul Muntaqim; Naufal, Sulthan (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This study examines how Arabic-language media construct meaning around alleged Gulf elite connections in the Jeffrey Epstein case, a transnational controversy involving issues of legitimacy, secrecy, and institutional authority. While framing research has widely explored domestic political scandals, limited attention has been given to how Arabic-language outlets frame transnational elite allegations within their institutional and geopolitical contexts. Positioned within discourse and media linguistics, this study analyzes how language operates as a symbolic resource in shaping political meaning. Using qualitative content analysis grounded in William A. Gamson’s interpretive package framework, the study analyzes two Arabic-language news articles published by France24 Arabic and WatanOnline. Framing devices (metaphors, catchphrases, exemplars, depictions, visual images) and reasoning devices (roots, appeals to principle, consequences) are systematically identified to reveal how interpretive packages are constructed. The findings indicate two contrasting orientations. France24 Arabic advances an institutional-procedural frame emphasizing documentation, formal political access, and state legitimacy. In contrast, WatanOnline constructs a network-of-influence frame highlighting secrecy, relational dependency, and concealed mediation. The study extends Gamson’s framing model to transnational elite scandals in Arabic media and demonstrates that framing functions as a linguistic mechanism shaping perceptions of elite legitimacy and political power.